The value of this expression depends on the values of x and of y. Since you have not bothered to share that information, it is not possible to evaluate the expression.
3y2 - 2y + 6xy - 4x = y(3y - 2) + 2x(3y - 2) = (y + 2x)*(3y - 2)
Yes and x = 2+square root of 6 or x = 2-square root of 6
4x + 20
perimeter of a square is 4x square that term (4x)(4x)and it gives you 16x2
x2 - 4x - 21 = (x-7)(x+3)
6xy+9y2
xy(7+2y-3x)-6xy
3y2 - 2y + 6xy - 4x = y(3y - 2) + 2x(3y - 2) = (y + 2x)*(3y - 2)
9x2 - 6xy + y2 - 81 = (3x - y)2 - 92 = (3x - y - 9)(3x - y + 9)
4
Yes and x = 2+square root of 6 or x = 2-square root of 6
x^2(2x - 3y)(4x^2 + 6xy + 9y^2)
3x2y - 4xy + 4x
35
The square root of 4x^2 is solved by first doing the square root of 4. This is plus or minus two - because -2 x -2=4. The square root of x^2 is x. So the answers are 2x or -2x. If your question was (4x)^2, then the answer would be 4x.
This is an equation known as a quadratic equation.x2-4x-96=0x2-4x=96-B +-SQUARE ROOT OF B-4AC OVER 2AA=1B=-4C=-96-4-4(1)(-96)=SQUARE ROOTOF 380ANSWER : 4-+ SQUARE ROOTOF 380 OVER 2Improved Answer:-x2-4x-96 = 0(x-12)(x+8) = 0x = 12 or x = -8
4x + 20